Energy level and thickness control on PEDOT:PSS layer for efficient planar heterojunction perovskite cells. (20th December 2017) - Wang, Chunhua; Zhang, Chujun; Tong, Sichao; Xia, Huayan; Wang, Lijuan; Xie, Haipeng; Gao, Yongli; Yang, Junliang
Abstract: Efficient planar heterojunction perovskite solar cells (PHJ-PSCs) with an architecture of ITO/PEDOT:PSS/CH3 NH3 PbI3 /PCBM/Al were fabricated by controlling the energy level and thickness of the PEDOT:PSS layer, where the PEDOT:PSS precursor was diluted with deionized water (H2 O) and isopropyl alcohol (IPA), i.e. W-PEDOT:PSS and I-PEDOT:PSS. The performance parameters of the PHJ-PSCs showed soaring enhancement after employing W-PEDOT:PSS or I-PEDOT:PSS instead of pristine PEDOT:PSS (P-PEDOT:PSS), resulting in an increase of the power conversion efficiency (PCE) of W-PEDOT:PSS-based PHJ-PSCs to 15.60% from 11.95% for P-PEDOT:PSS-based PHJ-PSCs. The performance improvement results from two aspects. On the one hand, as compared to P-PEDOT:PSS, the occupied molecular orbital energy (HOMO) level of dilute PEDOT:PSS showed an impressive decrease and can well match the valence band of CH3 NH3 PbI3 film, resulting in less energy loss and a significant improvement in the open-circuit voltage ( V oc ). On the other hand, the dilute PEDOT:PSS could produce a thinner film as compared with the P-PEDOT:PSS, which also played an important role in the performance of the PHJ-PSCs. Furthermore, the electrochemical impedance spectroscopy (EIS) results indicated that the interface between perovskite and PEDOT:PSS was greatly improved by employing W-PEDOT:PSS or I-PEDOT:PSS, leading to an obvious decrease in the series resistance ( R s ) and an increase in the recombination resistance ( R rec ). The research demonstrated that diluting PEDOT:PSS with a common solvent, such as H2 O and IPA, is a feasible low-temperature way of achieving efficient PHJ-PSCs.